Supporting Families and Professionals to Understand the Role of Hearing Technologies for Students Who Are Deaf or Hard of Hearing - Pam Millett; Imran Mulla (Education Sciences)
The use of hearing technology is one of the most effective strategies for providing access to spoken language and the auditory environment for students who are deaf or hard of hearing. In recent years, rapid advancements in hearing technologies have significantly improved access to spoken languages for learners of all ages. As part of the Special Issue “Educating Deaf Students in the 21st Century: A Changed and Changing Context”, this article describes how changes in hearing technology are related to changes in where and how students who are deaf or hard of hearing are educated. This article is designed to provide a foundation of knowledge about today’s hearing technologies for families, educators, and professionals such as speech–language pathologists or early childhood educators who support families and students. It provides an overview of hearing technology options, how they are prescribed and fit, and how benefits for language and literacy development can be evaluated. Barriers to effective use and future directions for hearing technologies are also described. The section “Highlights for Educators and Families” in the article discusses the practical application of this information to the work of those supporting students who are deaf or hard of hearing at home, at school, and in the community.